Work Overload, Stress Kerja Dan Gender Dalam Lingkungan Kerja - Nidya Novalia .; Susanti Saragih . (Universitas Kristen Maranatha, 2010)
This research aims to know the employee perception towards work load and the implication towards work stress for the employee. This research has also been done to examine the perception between man and woman in connected to the work load influence towards work stress. This research samples are 75 employees of Telkom Limited Corporation in Bandung. Both of tested hypotheses support by the previous research. The first hypothesis result shown that work overload ifluent significantly toward work stress for the employees. Futhermore, the second hypothesis described that work overload significantly influenced to the man employees and workload for the woman employees seem not to be influent significantly. As a result, there are some differences in workload influence toward work stress in man and woman employees. As an implication, this research suggested that human resource manager shall control the workload that is given to those employees balanced and considered the gender aspect in job description. This is important because man and woman have some different perception about workload.Keywords: work overload, work stress, gender.